HUBUNGAN PENDIDIKAN, KETERPAPARAN INFORMASI DAN PARITAS DENGAN TINGKAT PENGETAHUAN MANAJEMEN LAKTASI PADA IBU PASCA SALIN DI RUANG NIPAS RUMAH SAKIT UMUM DAERAH KOTA MAKASSAR - Desi Eka Prawtiwi (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2021)
Lactation management is one of the program efforts of MCH (Maternal and Child Health). If lactation management is not implemented, it will have an impact on reducing breastfeeding, resulting in an increase in malnutrition and malnutrition, which in turn will lead to an increase in morbidity and infant mortality. The aim of this study was to determine the relationship between education, exposure to information and parity with the level of knowledge of lactation management among postpartum mothers in the postpartum ward at the Makassar City regional general hospital. This research method uses analytical research methods with a "survey" approach with the Accidental Sampling technique. The research was carried out in the Nipas Room at Makassar City Regional Hospital with a sample size of 38 respondents. The research results show that education is p=0.004, exposure to information is p=0.005 and parity is p=0.000, so it is said that p<?. In conclusion, it is said that there is a relationship between education, exposure to information and parity with the level of knowledge of lactation management in postpartum mothers in the postpartum room at the Makassar City Regional General Hospital. The suggestions from this research are that breastfeeding mothers at the Makassar City Regional Hospital understand more about how to breastfeed properly and correctly and can take part in health education about breastfeeding